Examining the Characteristics of Intercity Bus Passengers in Michigan. Issue 1 (January 2014) - Sperry, Benjamin R.; Warner, Jeffery E.; Pearson, Robert G.
The Michigan Department of Transportation (DOT) supports a state-wide network of intercity bus services, including five routes operated under the FTA Section 5311 (f) program. To assist with planning activities for the state's intercity bus network, the Michigan DOT conducted an onboard survey of intercity bus passengers in the state in spring 2011. The Texas A&M Transportation Institute (TTI) was retained to analyze the 533 surveys obtained from this effort. This paper presents the results of the TTI analysis of the Michigan DOT spring 2011 intercity bus surveys. The survey results showed that three-quarters of the intercity bus passengers were from urban areas and the remaining one-quarter were from rural areas. Most passengers were traveling for personal reasons such as visits to family or friends or vacation. One-third of the surveyed passengers were from zero-vehicle households. If the bus service were not available, 59% of the passengers would drive, 19% would use an airplane, and 22% would not make the trip. Of zero-vehicle households, 31% of passengers would not make the trip; this result indicated a key role for the intercity bus service in supporting personal mobility. Other demographic groups that benefitted from the service included females and persons with annual household income less than 20, 000; both groups had a higher propensity not to make the trip in the absence of the bus service. The findings from the survey suggested that the Michigan intercity bus network was a critical transportation option for residents and visitors in the state and that bus passenger onboard surveys provided valuable information to support planning efforts.